2023
DOI: 10.3390/antiox12040907
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Natural Antioxidants in Female Reproduction

Abstract: Oxidative stress (OS) has an important role in female reproduction, whether it is ovulation, endometrium decidualization, menstruation, oocyte fertilization, or development andimplantation of an embryo in the uterus. The menstrual cycle is regulated by the physiological concentration of reactive forms of oxygen and nitrogen as redox signal molecules, which trigger and regulate the length of individual phases of the menstrual cycle. It has been suggested that the decline in female fertility is modulated by path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 169 publications
1
15
0
Order By: Relevance
“…Their action is primarily aimed at the endocrine and genital systems. It was established that the content of some vitamins is increased in many endocrine organs (Koshovyj, 2004;Jennings, 2014;Vašková, et al, 2023). Considering the information mentioned above, it can be concluded that the mentioned organs related to the reproductive system need more vitamins.…”
Section: Impaired Reproductive Function Due To Deficiency or Excessmentioning
confidence: 99%
“…Their action is primarily aimed at the endocrine and genital systems. It was established that the content of some vitamins is increased in many endocrine organs (Koshovyj, 2004;Jennings, 2014;Vašková, et al, 2023). Considering the information mentioned above, it can be concluded that the mentioned organs related to the reproductive system need more vitamins.…”
Section: Impaired Reproductive Function Due To Deficiency or Excessmentioning
confidence: 99%
“…Iron contributes to oxygen transport and energy metabolism [ 86 ], factors that can indirectly impact reproductive functions. Antioxidant vitamins like A, E, and C are particularly crucial in counteracting oxidative stress through the release of electrons to free radicals (Structure of vitamins in DPP highlighted in Figure 5 ), which can have detrimental effects on sperm quality and reproductive organs [ 87 , 88 , 89 ]. By neutralizing free radicals, these vitamins can protect sperm from DNA damage, improve motility, and enhance overall fertility [ 90 ].…”
Section: Exploring Mechanisms: How Date Palm Pollen Composition Influ...mentioning
confidence: 99%
“…Incorporating these foods in one's diet can bolster the body defenses against OS, possibly enhancing oocyte health and overall reproductive functionality. 78 Supplemental Antioxidants: These are intensified antioxidant formulations available in capsule or powder form. Taking these supplements can be particularly advantageous for females with recognized antioxidant deficits or distinct reproductive challenges related to OS.…”
Section: Natural and Supplemental Antioxidants: Benefits And Potentia...mentioning
confidence: 99%